GIS application in abiotic risks regionalization for spring barley - Středa, Tomáš; Cerkal, Radim; Hájková, Lenka; Chuchma, Filip; Khel, Tomáš; Klimešová, Jana (Contributions to Geophysics and Geodesy, 2020)
In recent years, there has been a noticeable uneven distribution of rainfall in Central Europe during the main vegetation season of most field crops. The rising air temperatures also increase the evapotranspiration demands of the environment and increase the frequency and length of heatwaves, which is a stress factor for plants. Using the GIS procedures, we identified the areas of significant abiotic risks occurring during the critical growth stages of spring barley (high air temperatures at the time of tillering and lack of soil moisture from the beginning of flowering to yellow ripening) with potential impact on grain yield in the Czech Republic. Unique datasets, including i) meteorological data, ii) phenological data, iii) pedological data, iv) land-use data, and v) geographic data, have been integrated and analysed using the sophisticated ArcGIS software environment. The method used in this study is universally applicable and allows comparisons at the local, regional, and supra-regional levels. The identification of risk areas will allow for a) finding tolerant varieties from problematic areas, b) locating the use of these varieties in risk areas and c) recommending and implementing adequate farming practices to reduce the impact of risk abiotic stressors on spring barley under current climate conditions. This will allow accurate estimation of weather impacts on spring barley grain yield in a particular year and precise application of countermeasures leading to reduced negative impacts on yield and the quality of spring barley production. Using the data and methods presented, we identified areas that correspond in good accordance to areas with spring barley yield deficits in dry years.